Regulation of CeA-Vme projection in masseter hyperactivity caused by restraint stress - Zhao, Ya-Juan; Chen, Ji; Liu, Yang; Pan, Lv-La; Guo, Yan-Xia; Zhang, Zhou-Ming; Li, Qiang; Chen, Yong-Jin (Frontiers in Cellular Neuroscience, 2024)
The overactivity of the masticatory muscles (bruxism or teeth clenching) is associated with stress exposure, and often leading to consistent muscle pain. However, the neural mechanism underlining it is not fully understood. The central amygdala (CeA), which is linked to stress-induced behaviors and physical reactions, projects directly to the mesencephalic trigeminal nucleus (Vme), which is crucial for oral-motor coordination. Thus, we hypothesized that the projections from the CeA to the Vme could be linked to stress-induced anxiety and overactivity of the jaw muscles. After establishing an animal model of restraint stress, we found that chronic stress could lead to noticeable anxiety-related behavior, increased masseter muscle activity, activation of GABAergic neurons in the CeA, and opposite changes in the excitability of multipolar GABAergic interneurons and pseudounipolar excitatory neurons in the Vme. Subsequently, through the utilization of anterograde and transsynaptic tracing in conjunction with immunofluorescence staining, we discovered that the neural projections from the CeA to the Vme were mainly GABAergic and that the projections from the CeA terminated on GABAergic interneurons within the Vme. Moreover, chemogenetically suppressing the function of GABAergic neurons in the CeA could effectively reduce anxiety levels and reverse the increase in the activity of the masseter muscles induced by stress. And, specifically inhibiting GABAergic projections from the CeA to the Vme via optogenetics could reduce the hyperactivity of the masseter muscles but not stress-induced anxiety. In conclusion, our findings indicate that GABAergic projections from the CeA to the Vme may play an important role in the masseter overactivity in response to chronic stress.